Hubungan pengetahuan dukungan suami dan keterjangkauan pelayanan kesehatan dengan minat menggunakan alat kontrasepsi jangka panjang - Nurqalbi Sampara; Hasriani Hasriani; Juwita Juwita; Fatimah Fatimah; Daswati Daswati (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Long-term contraception (MKJP) is an effective, safe, and highly successful method of contraception, but its use in the community is still relatively low. Purpose: To determine the relationship between knowledge, spousal support, and accessibility of health services with mothers' interest in using MKJP. Method: This was an analytical study with a cross-sectional design. The population in this study consisted of all mothers of childbearing age who were LCP acceptors and non-acceptors in the working area of the Bangkala Community Health Center. The research sample was determined using proportional random sampling. The research instrument used a structured questionnaire. Data analysis was performed using univariate and bivariate analysis using the Chi-Square test and multivariate analysis using multiple logistic regression. Results: There was a significant relationship between knowledge (p=0.002 < 0.05), husband's support (p= 0.047 < 0.05), and accessibility of health services (p= 0.031<0.05) with mothers' interest in using MKJP. The variable that had the most influence on interest was husband support, with the highest odds ratio (OR). Conclusion: This study concluded that increasing knowledge through appropriate education, strengthening husband support, and improving access to and affordability of health services can increase mothers' interest in using MKJP.